Keterampilan Menulis Teks Berita Menggunakan Metode Discovery Learning - Wirda Linda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effect of discovery learning method on writing news text skills. The research method used is an experimental research method with discovery learning approach. The results showed that the mean value of the experimental class was 83.78 with a standard deviation of 16.74 which were well qualified. Whereas in the control class the average value is 69.82 with a standard deviation of 15.87, which is more than adequate. The bivariate test results showed that the value of Ftable 3,4> Fcount 1.1095 and the analysis results obtained Tcount 3.061 and Ttable 1.68. The average score of the experimental class writing ability is higher than the control class. In conclusion, there is a significant effect of the use of the discovery learning method on the skills of writing news texts in class VIII students of SMP Negeri 4 Lareh Sago Halaban. Keywords: Discovery Learning Method, News Text Writing